The Promise of Functionalized Chitosan-Based Self-Healing Hydrogels - Md. Mahamudul Hasan Rumon; Mohammad Sayem; Sajal Kumar Halder; Razia Sultana Brishti; Ashish Das; Md. Ashraful Hasan; Md Salman Shakil (Advances in Polymer Technology)
Recent advancements in biomedical engineering have shed light on the remarkable capabilities of self-healing hydrogels, particularly those derived from chitosan (CHS) or its derivatives. These hydrogels exhibit noteworthy properties such as self-healing (SH), biocompatibility, and responsiveness to various stimuli like pressure, temperature, and pH. Recently, different therapeutic approaches, especially gene therapy and chemotherapy, have been explored through the incorporation of CHS-based hydrogels with therapeutic agents. Despite their promise, the clinical application of CHS hydrogels has been limited owing to an inadequate combination of physical and chemical properties, resulting in uncontrolled swelling and suboptimal SH behavior, particularly in terms of mechanical properties. This comprehensive review will explore the mechanistic understanding of various functionalized CHS, shedding light on their ability to offer desired SH properties while enhancing swelling behavior. These advancements are crucial for applications in tissue engineering and wound management. This comprehensive review aims to serve as a guide to CHS-based self-healing hydrogels, emphasizing their potential in addressing diverse challenges in the field of biomedical engineering.